Membimbing Siswa Menulis Dan Menerbitkan Karya Buku Anak Melalui Gerakan Literasi Sekolah - Ery Maritim (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article discusses best practices in guiding students to write and publish works through the school literacy movement at SD Negeri 02 Tanjungsari. The purpose of this paper is to provide insight into effective approaches and strategies in developing students' writing skills as well as encouraging them to publish work. This paper describes some best practices that can be applied in the context of the school literacy movement. First, it is important for schools to create an environment that supports and encourages students to write. This can be done through the establishment of reading corners in the classroom, literacy groups, creative spaces, and support from school residents. Giving special time to writing, providing relevant resources, providing appropriate guidance and guidance to students in the writing process are also important factors in increasing students' interest and motivation in writing. Teachers can use an inclusive and differentiated approach to ensure that every student gets support that suits their needs. The provision of constructive feedback and the opportunity to revise writing are also important aspects of guiding students in writing. The importance of publishing students' works as an effort to motivate them and provide a sense of achievement. Guiding students to write and publish work through the school literacy movement requires a holistic and structured approach. By creating a supportive environment, providing appropriate guidance, schools can motivate and help students develop writing skills as well as appreciate the value of their works.